Omni Utility Robotic Systems (O.U.R.S) - Ong, Zi Feng (2019)
Omni Utility Robotic System (O.U.R.S), is a mobile, interactive robotic installation that employs the knowledge and perception of the viewer to achieve a complicated task with a simple algorithm. The hand-made robot, named HibA, will request the viewer to pilot it to a randomly selected student’s booth, in hope to direct more viewers to all student’s work, in which, increase the student’s exposure during the Final Year Project (FYP) exhibition, one at a time. HibA is a physical manifestation of the synthesis between science and art, whereby it utilizes numerous sophisticated sensors and electronics, as well as multiple microcontroller to bring a piece of the artist’s imagination, into our reality.